Analysis of Tourist Motivation and Return Visit Intention to the Bendhung Lepen Tourism in Yogyakarta - Fadilla Ristya Aminda; Dinda Dewi Aisyah; Ahmad Rif’an Khoirul Lisan (Politeknik Sahid, 2026)
This research aims to analyse the socio-economic characteristics of visitors, the purpose of their visit, the number of visits, and tourist motivation and revisit intention in Bendung Lepen, Yogyakarta. The research used a survey method with a sample size of 60 tourists. The data were analysed using a quantitative descriptive approach. The results of the research show that visitors to Bendung Lepen are, on average, young and adults in the range of 15-42 years with an average length of education of 7-12 years, have no dependents, and an income of IDR 1,000,000 – IDR 2,000,000. Most tourists visit for recreational purposes, with an average frequency of 1-2 visits per year. The motivation for tourists to visit Bendung Lepen is due to the beautiful views (physical motivation), being invited by friends/family (social motivation), and other factors such as proximity, educational activities, and the availability of public facilities. As many as 91.67% of visitors expressed interest in returning because it was conveniently located near their homes, offered affordable recreational activities, was a beautiful and exciting place, and was child-friendly.